Associations Between Gender, Torture, and Health: A 5-Year Retrospective Cohort Analysis. Issue 3 (3rd April 2023) - Hoffman, Sarah J.; Shannon, Patricia J.; Horn, Tonya L.; Letts, James; Kondes, Zoe; Mathiason, Michelle A.
Abstract: Our purpose was to identify longitudinal associations between torture exposure, physical and mental health outcomes, and gender in a cohort of 143 war-affected Karen adults five years post resettlement. Results showed that participants who self-reported primary torture experiences had higher rates of certain mental and physical health diagnoses. We observed gender differences in health over time in the cohort. Findings have implications for how primary care and public health providers implement war trauma screening tools and timelines, targeted healthcare services, and community resources to promote health and prevent disease in populations that have trauma from torture or war.